Dutch Culture Overseas : Praktik kolonial di Hindia Belanda, 1900-1942 - Gouda, Frances (Serambi ilmu Semesta, 2007)
Judul Asli : Dutch Culture Overseas : Colonial Practice in the Netherlands Indies 1900-1942